Penerapan Model Coperative Learning Tipe Examples non Examples Menggunakan Media Pembelajaran Visual Dalam Meningkatkan Keaktifan Siswa Pada Pembelajaran IPA di Kelas V SD Negeri 064/XI Kota Sungai Penuh - Lydia Marlina (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study applies the example non example learning model to improve student learning activities in class V science lessons at SDN. 064 / XI Kota Sungai Penuh on animal movement materials has been carried out in two cycles. The results of research conducted in cycles I and II at SDN 064 / XI Kota Sungai Penuh. The results of observations in cycles I and II are in the form of observation data on student learning activities during the learning process. Based on the results of observations in cycle I, it can be seen that the teacher teaching in learning is good. The average value obtained by the teacher in planning and implementing learning was 86.95%, with details of the value at the first meeting of 86.95% and 86.95% in the second meeting. But the teacher has not been maximal in carrying out learning activities. In cycle II, the teacher made improvements to deficiencies in cycle I learning. The teacher carried out learning activities with a better example non example model. The teacher is able to integrate the material to be studied with what has been learned to students related to the material to be studied. With these improvement efforts, the value for teaching teachers can increase from cycle I. The average scores in cycle II reached 91.30% and 95.65% with a classical average of 93.47%.